Insilico and Invitro anthelmintic properties of phytocompounds in Rostellularia quinquangularis (J. Koenig ex Roxb.) Nees - D S N B K, Prasanth; Achanti, Suneetha; Kumar , Vijaya; Panda, Siva Prasad; Jash, Rajiv; Obilineni, Iswarya; Mokkapati, Poojitha; Chaganti, Pavithra; Katneni, Sandeep; Mohammad, Beebi Ayesha (Iranian Journal of Pharmaceutical Sciences, 2023)
The present study aimed to evaluate the anthelmintic activity of various extracts of Rostellularia quinquangularis (R. quinquangularis) against adult Indian earthworms (Pheretima posthuma). Petroleum ether extract (PERQ), ethyl acetate extract (RQEA), and ethanol extract (RQEE) of R. quinquangularis were tested at different concentrations (10, 20, 50, and 100 mg/mL), along with the positive control (albendazole) and negative control (normal saline). Anthelmintic activity was assessed based on the duration of paralysis and mortality. The RQEE extract showed significant anthelmintic activity, with the highest activity observed at a concentration of 100 mg/mL, exhibiting paralysis time of 1.62 min and death times of 19.9 min, compared to the standard albendazole. Further, HR LC-MS analysis of the RQEE extract revealed the presence of various phytoconstituents based on m/z signals. Molecular docking analysis using AutoDock Vina indicated that Columbianetin, Dunnione, Cryptochlorogenic acid, Gaylussacin, Luvangetin, and Albendazole showed docking scores of -8.1, -7.9, -7.4, -7.3, -7.2, and -6.8 Kcal/mol, respectively. These results suggest that R. quinquangularis possesses potent anthelmintic activity, supporting its traditional use in medicinal practices.